Prediksi Ketepatan Waktu Lulus Mahasiswa Menggunakan Algoritma C4.5 Pada Fakultas Dakwah Dan Ilmu Komunikasi UIN Raden Intan Lampung - Fiqih Satria; Zamhariri Zamhariri; M Apun Syaripudin (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Student graduation data is very important for universities because it is used in the accreditation process. Data continues to grow and is ignored because it is rarely used. Data of graduating students can provide useful information if processed optimally. This study processes data using data mining to obtain information in the form of a prediction of student graduation punctuality. The method used is the C4.5 algorithm. The criteria used are gender, regional origin, type of school origin, ranking and entry point. In its application, the C4.5 algorithm can be used in predicting student graduation times with a precision value of 70.70%, 60.4% recall, and 58.2% accuracy. In measuring the performance of the algorithm in pattern recognition or information retrieval it is recommended to use a minimum of two parameters namely precission and recall to detect bias, therefore in this study the F-Measure calculation is used. From the calculation of the F-Measure obtained a value of 71% which means that the C4.5 algorithm is considered good in classifying and predicting students who graduate on time